Implementation of Principal's Total Quality Management (TQM) in Improving Teacher Professional Competence at Private Elementary School - Nunung Kurniasih; Iim Wasliman; Teti Ratnawulan; Agus Mulyanto (CV. AFDIFAL MAJU BERKAH, 2022)
This study aims at describing the implementation of Principal’s Total Quality Management (TQM) in Improving Teacher Professional Competence in Private Elementary Schools. This qualitative research uses a case study method through observation, interviews, and documentation techniques at Elementary School’s Lab school of UPI Cibiru, Bandung Regency and Elementary School’s Lab of Al Azhar Syifa Budi Parahyangan, West Bandung Regency. The conclusion of the research is that the implementation of the Principal's Total Quality Management (TQM) in improving the professional competence of teachers in both schools has been going well, on the contrary they have not implemented the TQM principles optimally. This is illustrated by the lack of integration of socialization activities at the planning stage and the lack of effective communication relationships with parents and other institutions. Thus, it is necessary to carry out further studies related to improving the professional competence of teachers in elementary schools to map the condition of teachers in the future.